Design Development of Punching and Bending Machine Combination - Fiqi Fendi; Yohanes Yohanes (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
This paper purpose is to study working pressure limit of the machine combination between blanking and punching process. The combination punch and bending machine in this study is a machine that belongs to the press type with the use of punch and die. This machine has a hydraulic drive with a maximum pressure generated of 700 bars. The engine performance is only able to withstand a working pressure of 27.7 bars. Therefore, the utilization of the working pressure must be increased to maximize the working pressure. The analysis was carried out on the machine with two methods, namely simulation and experiment. The simulation method was carried out using Autodesk Inventor software to design and simulate in order to find out the critical points that occur on the machine. It was given working pressure according to the permitted safety factor of 1.5. The experimental method was carried out by measuring the voltage using a Strain gauge sensor positioned at the critical point obtained in the simulation and measuring the deflection using a dial indicator. From these tests, it was found that the initial working pressure before being optimized was 27.7 bars to 49.5 bars after being optimized.